METHODOLOGY OF DOMESTIC STUDIES OF MEDICINAL DRUGS NEED AND THEIR CONSUMPTION - N. B. Dryomova; L. V. Kobzar; E. A. Korzhavych (Фармация и фармакология (Пятигорск), 2015)
At the current development stage of Russian healthcare rational use of limited financial resources for the fullest satisfaction of population's need in medicinal drugs acquires a special importance. Therefore, the issue about knowledge of experts in determination of need in drugs and evaluation of the consumption, as well as methods applied for these scientific and practical tasks resolution has a critical character. The purpose of our work is to characterize the development of research methodology of medicinal drugs need and their consumption in Russia. We have revealed the dynamics and tendencies of analyzed scientific direction development, leading scientists, principal methods, and study objects using scientometric methods of content-analysis and scientific works calculation (dissertations autoab-stracts). We have established the fact of significant change of methodology beginning with 2000 comparing with a period 1970-1980s. According to authors' opinion this was conditioned by objective need in problem solving connected with pharmaceutical support in the frameworks of state guarantees.